Implementation of the Adiwiyata Program in Formation of Student Creativity and Concern for the Environment at UPT SPF SD Inpres Lanraki 1 Makassar City - Harmiah Hb; Rosleny Rosleny; Sulfasyah Sulfasyah (Edumaspul: Jurnal Pendidikan, 2022)
This study aimed to determine the strategy in implementing the Adiwiyata program in shaping students' creativity and caring attitude towards the school environment as well as supporting factors and inhibiting factors during the implementation of this program in the school. This research employed a descriptive qualitative design. Data were collected through interviews, observation, and documentation. This study used data analysis techniques with the stages of data collection, data reduction, data presentation, and conclusion. The result showed that the implementation of the Adiwiyata program in shaping students' creativity was carried out by aligning the school's vision and mission with Adiwiyata program indicators which were manifested in the habit of bringing food/drinks from home, sorting wastes according to the type of waste and green hose processing. Students' caring attitude towards the environment was formed through the implementation of the Adiwiyata program with environment-based habituation activities such as maintaining the cleanliness of the classroom and school environment, Saturday clean activities, garbage disposal in its place, implementing the LISA program (Lihat Sampah Ambil) and one pot plant one student program. The supporting factors in implementing the Adiwiyata program included the integration with the school's vision and mission, strategic school location, adequate supporting facilities and infrastructure, and collaboration with all teachers and the Adiwiyata team. While the inhibiting factors of the Adiwiyata program were the school environment which often flooded during the rainy season, lack of communication with outsiders, and the limited allocation of funds for Adiwiyata activities.